PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT ONOLALU - Samanoi Halowo Fau; Progresif Buulolo; Anskaria Simfrosa Gohae (JURNAL EKONOMI DAN BISNIS NIAS SELATAN, 2022)
The scope of this research is a study of the influence of the work environment on the performance of employees in the sub-district office of Onolalu. The purpose of this study was to determine the effect of the work environment on employee performance at the Onolalu District Office. The research method used is simple linear regression analysis through research instrument testing, classical assumption test, and hypothesis testing (t-test and coefficient of determination test). The population and sample in this study were 33 employees. The data analysis method used is simple linear regression analysis. The results of this study indicate that the work environment (X) has a positive and significant effect on employee performance at the Onolalu District Office. This study can be concluded that the work environment (X) has a positive and significant effect on employee performance at the Onolalu District Office.